IMPACT OF EXOGENOUS PROLINE APPLICATION ON PHYSIOLOGY, BIOCHEMISTRY, AND FORAGE QUALITY OF MAIZE (Zea mays L.) UNDER DROUGHT STRESS - Timuçin TAS; Orkun BABACAN; Tülay Turgut GENÇ; Yahya ISIK (Journal of Animal and Plant Sciences, 2026)
Drought is a real threat to crop production, and crops like maize, which consume high amounts of water, are adversely affected by the lack of adequate soil moisture. The information on drought tolerance mechanism of maize during the seedling stage is essential to alleviate the negative effect of drought stress. This study was conducted to determine the effects of exogenous proline application on morphology, physiology, biochemical characteristics, feed quality, and enterobacteriacae parameters of a commercial maize variety grown under drought conditions. Deficit irrigation had detrimental effects on maize growth, while exogenous proline application mitigated the negative effects of drought and improved the maize growth. The chlorophyll content of maize plants was negatively affected by drought, but proline treatments regulated chlorophyll degradation by up to 90%. The concentrations of hemicellulose, cellulose, and lignin increased under drought conditions during the seedling stage, which led to accelerated plant aging. The increase in drought intensity led to higher levels of oxidants (such as hydrogen peroxide) and increased antioxidant activities. Exogenous proline application enhanced the activities of antioxidant enzymes (superoxide dismutase, peroxidase, and catalase) and reduced the harmful effects of hydrogen peroxide. The results revealed that proline application during the seedling period reduced the water consumption of maize plantsby25- 40%. In addition, leaf chlorophyll content is a practical and cost-effective parameter for assessing maize drought stress and tolerance levels <p class="MsoNormal" style="text-align: justify; line-height: normal; border: none; mso-border-bottom-alt: solid windowtext .5pt; padding: 0in; mso-padding-alt: 0in 0in 1.0pt 0in; margin: 6.0pt 0in .0001pt 0in;">Key words: Drought stress, Exagenous proline, antioxidant activities, Enterobacteriaceae <span lang="TR" style="font-size: 10.0pt; line-height: 107%; font-family: 'Times New Roman',serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; color: black; mso-ansi-language: TR; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (<span lang="TR" style="font-size: 10.0pt; line-height: 107%; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'DengXian Light'; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; color: black; mso-ansi-language: TR; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">https://creativecommons.org/licenses/by/4.0
Keywords: Drought stress; Exagenous proline; antioxidant activities; Enterobacteriaceae